Smart ecotourism planning in chiang mai using traveling salesman problem - Wapee Manopiniwes (2019)
© 2019 Association for Computing Machinery. A well-planned vacation can bring every visitor not only higher enjoyment of his or her trip but allows to maximize efficiently spent time within the budget constraints. This research proposes the suggested routes for ecotourism destinations in Chiang Mai, Thailand by using the traveling salesman problem (TSP) method. Chiang Mai has been noticed as the destination of ecotourism because of a rich and beautiful natural resources. It is convenient for tourists to have a web-based platform providing all updated destinations and suggested plan about ecotourism. As a pilot study, the most popular ten ecotourism destinations were collected from the secondary data observation. The study is applied the advantages of TSP technique to the tourism context in order to create the optimal travel plans under the different time constrains. Then webbased programming show the created trip plan and travel itinerary available for all tourists to download.